2015
DOI: 10.1016/j.neuroscience.2015.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Functional differences in face processing between the amygdala and ventrolateral prefrontal cortex in monkeys

Abstract: The ability to categorize social information is essential to survive in a primate's social group. In the monkey brain, there are neural systems to categorize social information. Among these, the relationship between the amygdala and the ventrolateral prefrontal cortex (vlPFC) has recently gained focus with regard to emotion regulation. However, the processing of facial information and the functional differences in these two areas remain unclear. Thus, in this study, we examined the response properties of singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
1
13
1
Order By: Relevance
“…The dmPFC cluster also includes area 45A, located in the caudal VLPF cortex. Functional data show that this sector is involved in multisensory processing of communication stimuli ( Romanski and Averbeck, 2009 ) and activates during action and face observation ( Nelissen et al, 2005 ; Tsao et al, 2008 ; Kuraoka et al, 2015 ), suggesting a role in communication behavior. Moreover, this region is activated during eye movement ( Premereur et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The dmPFC cluster also includes area 45A, located in the caudal VLPF cortex. Functional data show that this sector is involved in multisensory processing of communication stimuli ( Romanski and Averbeck, 2009 ) and activates during action and face observation ( Nelissen et al, 2005 ; Tsao et al, 2008 ; Kuraoka et al, 2015 ), suggesting a role in communication behavior. Moreover, this region is activated during eye movement ( Premereur et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to fearful visual stimuli leads to changes in electrical activity of the amygdala in humans (Morris et al, 1996 ) and monkeys (Leonard et al, 1985 ; Nakamura et al, 1992 ; Kuraoka and Nakamura, 2006 , 2007 ; Gothard et al, 2007 ; Hoffman et al, 2007 ; Kuraoka et al, 2015 ) although the amygdala does not receive any direct retinal innervation. LeDoux ( 1990 , 1994 ) suggested that visual threats were primarily conveyed to the limbic system via the SC-pulvinar pathway, the so-called “low road” (Figure 1 ).…”
Section: The Low Road High Road Debatementioning
confidence: 99%
“…In fact, the ventrolateral prefrontal cortex (VLPC) is connected both with temporal sectors participating to the visual coding of biological motion (Barbas, 1988; Petrides and Pandya, 2002; Gerbella et al, 2010, 2013; Borra et al, 2011) and, as demonstrated in the present study, with the mouth MNs sector. In addition, VLPC contains neurons responding to visual stimuli of faces and of facial communicative gestures (Ó Scalaidhe et al, 1997, 1999; Sugihara et al, 2006; Romanski and Diehl, 2011; Kuraoka et al, 2015). It is also likely that information related to facial expressions and/or its emotional content could reach the F5/opercular region through other pathways involving the orbitofrontal, insula and the amygdala (see below for further elaboration).…”
Section: Introductionmentioning
confidence: 99%